2014
DOI: 10.2174/1874364101408010051
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Confocal Microscopic Evaluation of Corneal Langerhans Cells in Dry Eye Patients§

Abstract: Purpose. To assess inflammatory involvement of cornea in dry eye by means of confocal microscopy, evaluating the presence and distribution of Langherans cells (LCs).Methods: 98 eyes of 49 subjects were enrolled: 18 subjects affected by Sjögren Syndrome Dry Eye (SSDE), 17 with Non-Sjögren Syndrome Dry Eye (NSSDE), 14 healthy volunteeers. Dry eye symptoms, tear film, ocular surface damage and corneal confocal microscopy were analized.Results: A significant increase of LCs density was observed at sub-basal nerv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
26
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 30 publications
1
26
0
1
Order By: Relevance
“…13 Alternatively, they might be related to corneal inflammation representing cells that are in a particular state of metabolic activation, induced by proinflammatory cytokines (IL-1 and TNF). 13,22 Interestingly, we found a progressive decrease in the number of hyperreflective stromal cells consistent with the use of topical cyclosporine administration during follow-up. This finding suggests that their presence is most likely to be related to the level of corneal inflammation and these cells could be used as a parameter to diagnose corneal inflammation and to follow its response to treatment (Figure 2).…”
Section: Discussionsupporting
confidence: 62%
“…13 Alternatively, they might be related to corneal inflammation representing cells that are in a particular state of metabolic activation, induced by proinflammatory cytokines (IL-1 and TNF). 13,22 Interestingly, we found a progressive decrease in the number of hyperreflective stromal cells consistent with the use of topical cyclosporine administration during follow-up. This finding suggests that their presence is most likely to be related to the level of corneal inflammation and these cells could be used as a parameter to diagnose corneal inflammation and to follow its response to treatment (Figure 2).…”
Section: Discussionsupporting
confidence: 62%
“…Patients with DED of any etiology have a higher LC density in their central cornea than healthy controls, with the highest densities found in autoimmune‐associated DED . LC were larger and had more or longer dendrites in DED patients than in healthy controls.…”
Section: Discussionmentioning
confidence: 98%
“…The observation in this study of an initial up‐regulation in corneal LCD in CLIDE versus controls at one and four weeks is consistent with previous reports of higher levels of corneal LCD in dry eye patients. Machetta and colleagues reported a higher LCD in the central cornea of patients with Sjögren syndrome dry eye (SSDE) (79 cells/mm 2 ) compared to those without dry eye (22 cells/mm 2 ) (p = 0.0031). In a similar study, Lin and colleagues reported a higher LCD in the central cornea of patients with both SSDE (128 cells/mm 2 ) and non‐SSDE (90 cells/mm 2 ) compared to those without dry eye (35 cells/mm 2 ).…”
Section: Discussionmentioning
confidence: 99%